Quasar Sightline and Galaxy Evolution (QSAGE) survey – I. The galaxy environment of O vi absorbers up to z = 1.4 around PKS 0232−04. Issue 1 (16th March 2019) - Bielby, R M; Stott, J P; Cullen, F; Tripp, T M; Burchett, J N; Fumagalli, M; Morris, S L; Tejos, N; Crain, R A; Bower, R G; Prochaska, J X
ABSTRACT: We present the first results from a study of O vi absorption around galaxies at z < 1.44 using data from a near-infrared grism spectroscopic Hubble Space Telescope Large Programme, the Quasar Sightline and Galaxy Evolution (QSAGE) survey. QSAGE is the first grism galaxy survey to focus on the circumgalactic medium at z ∼ 1, providing a blind survey of the galaxy population. The galaxy sample is H α flux limited ( f (H α) > 2 × 10 −17 erg s −1 cm −2 ) at 0.68 < z < 1.44, corresponding to ≳0.2–0.8 M⊙ yr −1 . In this first of 12 fields, we combine the galaxy data with high-resolution STIS and COS spectroscopy of the background quasar to study O vi in the circumgalactic medium. At z ∼ 1, we find O vi absorption systems up to b ∼ 350 kpc (∼4 R vir ) from the nearest detected galaxy. Further, we find50 per cent of ≳1 M⊙ yr −1 star-forming galaxies within 2 R vir show no associated O vi absorption to a limit of at least N (O vi ) = 10 13.9 cm −2 . That we detect O vi at such large distances from galaxies and that a significant fraction of star-forming galaxies show no detectable O vi absorption disfavours outflows from ongoing star formation as the primary medium traced by these absorbers. Instead, by combining our own low- and high-redshift data with existing samples, we find tentative evidence for many strong ( N (O vi ) > 10 14 cm −2 ) O vi absorption systems to be associated with M ⋆ ∼ 10 9.5–10 M⊙ mass galaxies ( M halo ∼ 10 11.5–12 M⊙ dark matter haloes), and infer that they may be tracing predominantly collisionally ionized gas within the haloes of such galaxies.